PERAN GURU DALAM IMPLEMENTASI KURIKULUM 2013: STUDI PADA TK MENTARI KEC. ABUNG SELATAN KAB. LAMPUNG UTARA - Tri Andiyanto (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
The curriculum is a vehicle for learning dynamic that needs to be developed and assessed continually ongoing in accordance with the existing developed community. The teacher’s role in the implementasi 2013, namely: a) the teacher haddiscussions in the process of preparation of the RPP; b) teachers write lesson plans through appropriate measure; c) teachers carry out a detailed study; d) the teacher as a facilitator; e) teachers provide character education; f) teachers guide students in learning in accordance with a scientific approach; g) teacher choose and use methods, media, and a variety of learning resources; h) teacher conduct authentic assesment; i) the teacher chooses and using valuation technique vary.